A study of a possible scenario of Zika virus outbreak and rapid intervention using a mathematical and computational simulation - Nieto Chaupis, Huber (2016)
From a mathematical model given by the integral Im,n=∫Pm(x)G(x)Jn(x)dx where Pm(x) a polynomial function, G(x) a Gaussian function, and Jn(x) is the integer-order Bessel function, we have performed simulations to evaluate the possible scenario of outbreak of Zika virus (ZIKV) in a big city. Our study is motivated from the outbreaks in Brazil (2007). We have assumed a list of probabilities which are connected to the number of cases in-risk which is changing in time. Also, the intervention is defined as the fraction ΔIm,n and it is selected by the Monte Carlo step. Simulations takes into account the rapid intervention that means the transfer of those identified (e.g. pregnant women) to save and clean areas away from the mosquitoes Aedes.